PRODUCTION PERFORMANCES OF DUROC PIG IN FAJAR SEMESTA INDAH INC. SINGKAWANG WEST KALIMANTAN - DOMI NIKO; AHMAD TOHARDI; YETI ROHAYETI (Jurnal Sains Pertanian Equator, 2019)
Starting a pig farming business, breeders have difficulty in determiningwhat kind of breed they want to farm because of the lack of conception andinformation about production performances of pig farming; thus, productionperformances tests are required. The results of production performances tests canbe a conception and information for pig breeder who wants to establish a farmingbusiness. The known production performances can be used as a means to increaselivestock productivity. Production performances that considerably determineprofit in pig farming business are litter size, birth mortality, birth weight, preweaning mortality, and weaning weight. The method used in this research issurvey method, the data used secondary data (company’s recording data) andprimary data (field data) from Duroc sows totaling 30 pigs in Fajar SemestaIndah Inc. Singkawang West Kalimantan. The results of the research show thatDuroc pig’s production performances are as follows: litter size 8,37±3,34 pigs,birth mortality 1,07±1,17 pigs or 12,75 % birth weight 1,47±0,25 kg, pre-weaningmortality 0,97±1,50 pigs or 15,26 % and weaning weight 6,63±1,63 kg.Keywords: Pig, Duroc, performances, production